Cognitive behavioural therapy for anxiety in psychosis: a systematic review and meta-analysis. Issue 3 (3rd July 2019) - Heavens, David; Odgers, Kelsey; Hodgekins, Joanne
ABSTRACT: Background : Anxiety is common in people with psychosis. Cognitive Behavioural Therapy (CBT) is an effective treatment for anxiety in people without psychosis. Given the prevalence of anxiety in those with psychosis, the efficacy of CBT in this population is important to consider. This review and meta-analysis therefore investigates the efficacy of CBT for anxiety in people with psychosis. Method : Twenty-nine studies were identified through systematic review, including controlled, uncontrolled and case report designs. Seventeen controlled and uncontrolled studies were included in the quantitative synthesis. Results : A medium, significant effect was found at post-treatment and follow-up when controlled and uncontrolled data were combined. For controlled between-groups data only, a small, significant effect was found at post-treatment and follow-up. The effect of CBT for anxiety on psychotic symptoms was investigated, resulting in a medium, significant effect for controlled and uncontrolled post-treatment data and a small, significant effect for controlled between-group data. Conclusions : CBT might have some effect in treating anxiety in people with psychosis. However, this review highlights a lack of scientifically rigorous studies in this area. Further research is required, including the use of well-designed randomized controlled trials (RCTs).